2009
DOI: 10.1016/j.polymer.2009.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of O2-plasma-treated thermoplastic fluoroelastomers under mechanical stretching

Abstract: Surface properties and structure of an oxygen-plasma-treated thermoplastic fluoroelastomer film under mechanical stretching were investigated using dynamic contact angle, X-ray photoelectron spectroscopy and field-emission scanning electron microscopy. The contact angle of water on the surface decreased from 96° to 36° by the plasma treatment. The contact angle increased under uniaxial stretching: the plasma-treatment effect decreased. This was considered to be due to a dilution of the plasma-oxidized chains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…This was investigated with thermoplastic fluoro-elastomer, samples of which were given oxygen plasma treatment (200 W, 60 s). Figure 9 shows the strain dependence of dynamic contact angle q with water on the surface of the oxygen plasma treated thermoplastic fluoro-elastomer [12]. Without surface treatment, q had a high value of 96° and remained constant regardless of deformation of the sample.…”
Section: Change In Effect Of Surface Treatment In the Uniaxial Deformmentioning
confidence: 99%
“…This was investigated with thermoplastic fluoro-elastomer, samples of which were given oxygen plasma treatment (200 W, 60 s). Figure 9 shows the strain dependence of dynamic contact angle q with water on the surface of the oxygen plasma treated thermoplastic fluoro-elastomer [12]. Without surface treatment, q had a high value of 96° and remained constant regardless of deformation of the sample.…”
Section: Change In Effect Of Surface Treatment In the Uniaxial Deformmentioning
confidence: 99%
“…During deformation process, semi‐crystalline polymers generally produce superstructures. The evolution of superstructures involves the variation of crystalline and amorphous phases, including orientation‐induced crystallization, crystal transition, chain orientation, fibrillary formation and cavitation and so forth 1–7 . Therefore, it is of great significance to study superstructure transformation and its correlations with stress–strain curves for preparing microporous membrane by dry process 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Structural studies of oriented PLLA reveals that stretching-induced crystallization is the straight cause of drastically enhancing in mechanical properties during stretching above the glass-transition temperature (T g ) of PLLA. [21][22][23] Structural studies of oriented PLLA reveals that stretching-induced crystallization is the straight cause of drastically enhancing in mechanical properties during stretching above the glass-transition temperature (T g ) of PLLA.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that biaxial or uniaxial stretching of semicrystalline polymers is an effective way to improve the mechanical properties, which is directly depended on the formation of superstructures. [21][22][23] Structural studies of oriented PLLA reveals that stretching-induced crystallization is the straight cause of drastically enhancing in mechanical properties during stretching above the glass-transition temperature (T g ) of PLLA. 24 Meanwhile, it is shown that the structure and performances of stretched PLLA highly depend on the stretch conditions, such as stretching temperature, stretch ratio, and rate.…”
Section: Introductionmentioning
confidence: 99%